PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK UNTUK MELATIH KETERAMPILAN BERPIKIR SISWA PADA TEMA 1 SUBTEMA 1 KELAS V SD - Sinaga, Annisa Irfyanti; Ananda, Lala Jelita (Universitas Negeri Medan, 2024)
This research aims to produce Big Book learning media that is valid, practical and effective in training students' thinking skills in class V at SDN 091324 Merek Raya. This research is development research that uses the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this research were class V teachers and class V students at SD Negeri 091324 Merek Raya. The object of research in this study is the validation, practicality and effectiveness of the Big Book learning media in training students' thinking skills. The data collection techniques used are interviews, tests, observation and documentation. The instruments used in data collection were teacher interview instruments, media design and media material validation questionnaires, educational practitioner questionnaires, student response questionnaires, and test questions. The results of the research show that the validation results by media design expert validators obtained an average score of 4.7 with a percentage result of 89% in the